Central banking in South and East Asia - Davies, S. Gethyn ([Hong Kong]: Hong Kong University Press, 1960)
This book gives an account of central banking and of its success in promoting development with stability in those under-developed countries of South and East Asia. It highlighted some of their challenges in trying to maintain domestic price stability and efforts made to remedy the situation through sound fiscal policies and suitable banking and credit structure and some flexibility in foreign exchange rate.
Includes index
Includes bibliographical references.
usc 27/09/2018
Loans
Keywords: Banks and banking, Central; Asia